Who are we when we go inside?:48 hours in the New York City justice system - Rourke, Micaeli (My University, 2019)
The Rikers Island Correctional Complex is as mysterious to American culture-atlarge as it is notorious. “For viewers of Law and Order,” writes journalist Kaitlin Menza in New York Magazine, “'Rikers is synonymous with 'worst place someone can be.' For criminal-justice advocates, it's a microcosm of everything wrong with the American prison system” (Menza, 2017). Spanning 167 hectares of land in the East River between the boroughs of Queens and the Bronx, the island is home to one of the world’s largest prison complexes (Alexander, 2017), and the second largest jail in the United States (Bogan, 2019). This was about all I knew about Rikers Island for most of my life. Admittedly, I spent two years living within three kilometers from the island and was wholly unaware of its proximity the entire time. In October of 2016, as I returned to America from South Africa for a short visit home, I was stopped at Immigration Control upon landing at JFK International Airport in New York City. A missed court appearance had resulted in a bench warrant for my arrest in my native state of Pennsylvania. It had been issued while I was abroad, over 7 months prior. I was subsequently arrested at the airport, arraigned, and remanded without bail to the Rose M. Singer Female Correctional Facility on Rikers Island. I was sentenced to spend the next fourteen days as a “fugitive from justice” detainee, awaiting out-of-state extradition. During that period of time I attempted to maintain a sense of purpose and perspective by documenting as many of the aspects of life inside the jail that I encountered there, as if it were a journalistic assignment similar to Nellie Bly’s groundbreaking work of American immersion journalism “10 Days in a Madhouse.” This longform narrative seeks to document and contextualize my personal experience within the New York City Department of Correction for the very first time.
A thesis submitted to the Department of Journalism and Media Studies, Faculty of Humanities,University of the Witwatersrand, in fulfillment of the requirements for the degree of Master of Arts. October 2019
Keywords: Prisoners--New York (State)--New York; Criminal justice, Administration of--New York (State)--New York